The smart cookie - John, Jory (Harper, an imprint of HarperCollins Publishers, 2021)
"This cookie has never felt like a smart cookie no matter how hard she tries, especially in comparison to all the clever cupcakes and brilliant rolls in the bakery. Will a dash of creativity and a sprinkle of confidence be enough to help her learn that perfect scores and having all the answers aren't the only ingredients for intelligence?"--